Transformasi TPS Menjadi TPS 3R (Reduce, Reuse, Recycle) Melalui Budidaya Maggot dan Pembuatan Pupuk Kompos (Lembaga Pengembangan Kinerja Dosen, 2025)
Suboptimal waste management in Kalijoso Village, Secang District, Magelang Regency, is a critical issue that impacts environmental sustainability and public health. The inefficiency of conventional waste disposal methods has led to increased waste accumulation, soil and water pollution, and the spread of diseases, which has significant consequences for local communities. To address these challenges, the local government and community organizations have embraced the principles of the 3R (Reduce, Reuse, Recycle) through a transformation of traditional waste disposal sites (TPS) into 3R TPS. The new approach focuses on sustainable waste management practices that reduce the amount of waste sent to landfills. One of the key strategies implemented is educational outreach to raise awareness about the importance of waste segregation and recycling. Additionally, training programs have been conducted to teach the community how to process organic waste, particularly through the cultivation of maggots using Black Soldier Fly (BSF) larvae. This method not only helps reduce the volume of organic waste but also provides a practical solution for transforming waste into valuable resources. The maggots cultivated during the demonstration are used as animal feed, which creates a sustainable circular economy within the community. Furthermore, composting organic waste results in high-quality compost that supports local agricultural activities. This has added economic value by reducing the need for chemical fertilizers, while simultaneously improving soil health. The role of the Salakan Hamlet Youth Organization has been instrumental in this initiative. They have successfully managed a waste bank, providing an organized and systematic approach to waste collection and recycling. This initiative has fostered a sense of community responsibility and has not only improved waste management practices but also contributed to the overall economic development of the village.